Bibliometric Analysis: Marginal Productivity and its Relevance Towards Modern Labor Wage Determination - Setia, Nanda; Rozalinda, Rozalinda; Hendra, Testru (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2025)
This study aims to analyze the development of scientific publications on Marginal Productivity and its relevance to determining modern labor wages during the period 2020 to 2025 using a bibliometric approach. Data was obtained from Scopus basic data by downloading article metadata in RIS and CSV formats, then processed using VOS viewer software with a minimum number of keywords of 5 out of 2,893 keywords, 207 of which met the threshold to produce three types of visualizations, namely network visualization, overlay visualization, and density visualization. The results showed that there were 558 publications related to the topic during the six years of observation with a downward trend from 113 articles in 2020 to 68articles in 2025. Network visualization revealed that